Membangun Motivasi (Self Transendence) Pendidik di MI Muhammadiyah Al-Muttaqien Sleman - Wulandari, Juwita Kusuma; Nugrahani, Robi’ah (Fakultas Tarbiyah, Institut PTIQ Jakarta, 2020)
The research, entitled Building Educator Motivation (Self Transcendence) at MI Muhammadiyah Al-Muttaqien aims to determine the role of the institution or the principal as a motivator to optimize teacher performance at MI Muhammadiyah Al-Muttaqien. This research is a research with a qualitative approach that is descriptive. The subjects of this study include principals and teachers who teach at MI Muhammadiyah Al-Muttaqien. The data collection techniques used were interviews and observation. The theory used is Maslow's Hierarchy of Need theory in which there are several levels of needs needed to increase work motivation. In research, this theory is used to determine the achievement of the spiritual needs of teachers who teach at MI Muhammadiyah Al-Muttaqien. Also, whether all the needs contained in Maslow's theory can be met by the institution so that it can increase the work motivation of teachers. The results showed that the role of institutions and school principals in increasing motivation, as well as means of rewarding the performance of teachers is really needed. However, there are shortcomings or limitations in terms of fund allocation and other things that make several things in the level of need not fulfilled. Even though there are deficiencies in this, the enthusiasm of the teachers to continue to teach and be sincere in conveying knowledge are important things that create self-transcendence.